The geography of banking: Evidence from branch closings. (6th October 2020) - Galardo, Maddalena; Garrì, Iconio; Mistrulli, Paolo Emilio; Revelli, Davide
Abstract: In the aftermath of the Great Recession, the number of bank branches declined in most developed countries. In this paper, we investigate how banks have downsized their branch networks in Italy, by comparing the pre‐ and post‐crisis spatial distribution of branches. By using a detailed data set that includes a wide set of controls for the characteristics of each bank branch, we estimate the probability of a branch being closed as a function of its distance from both proprietary and competitors' branches. We find that banks are more prone to close branches in those areas where other proprietary branches are closer and where competitors' branches are closer. This indicates that, since the start of the crisis, banks have closed branches especially in those areas where their proprietary network was relatively more populated and the competition was fiercer.